Data science projects with Python : a case study approach to gaining valuable insights from real data with machine learning - Klosterman, Stephen (Packt Publishing, 2021)
Ideal for anyone who is just getting started with machine learning, this hands-on data science book will give you experience building predictive models using industry-standard tools and techniques. It will help you develop the skills and understanding to generate valuable insights and make data-driven business decisions.